FORMULASI DAN UJI EFEKTIVITAS ANTIBAKTERI SEDIAAN MOUTHWASH DARI EKSTRAK DAUN KEMANGI (Ocimum x africanum L.) TERHADAP BAKTERI Staphylococcus aureus - Voen-Na, Cut Dara; Wardani, Tatiana Siska; Wicahyo, Septian Maulid (Universitas Imelda Medan, 2025)
The oral cavity is susceptible to bacterial infections because it has direct exposure to the outside environment, one of which is Staphylococcus aureus, which can cause oral health problems. The use of mouthwash as an additional treatment helps maintain optimal oral hygiene. Basil leaves (Ocimum x africanum L.) contain secondary metabolite compounds that have the potential to inhibit the growth of S. aureus. This study aims to determine the physical quality test of mouthwash of basil leaf extract and test its antibacterial effectiveness against S. aureus. This research method is laboratory experimental. Basil leaf simplicia powder (Ocimum x africanum L.) is macerated with 96% ethanol. Mouthwash formulations are made in concentrations of 4%, 6%, 8%, and 10%. Testing was carried out using the disc diffusion method to assess the antibacterial effectiveness against S. aureus ATCC 25923. Physical quality tests are also carried out on mouthwash preparations. The data from the antibacterial test results were analyzed using the One-Way ANOVA method. The results showed that the mouthwash preparation formula of basil leaf extract had good physical quality in terms of organoleptics, pH, specific gravity, viscosity, and clarity. The results of the statistical test showed a significant difference in the diameter of each group (P<0.05); mouthwash preparation at F4 (10%) had an inhibitory power against S. aureus bacteria of 8.46 mm with a bacterial inhibition zone of the medium category.